2018
DOI: 10.1111/1346-8138.14531
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of incident psoriasis in end‐stage renal disease patients on chronic hemodialysis: A nationwide population‐based cohort study

Abstract: Patients with end-stage renal disease (ESRD) on chronic hemodialysis (HD) experience chronic inflammation and immune dysregulation; whether these affect the development of chronic inflammatory disease such as psoriasis is unknown. We aimed to investigate the impact of ESRD on the development of psoriasis. We performed a retrospective cohort study using records between 1999 and 2013 from Taiwan's National Health Insurance Research Database. Among 74 916 patients with ESRD on chronic HD and the control group com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Psoriasis is also significantly comorbid with other autoimmune diseases, such as bullous pemphigoid [20][21][22][23][24]. Psoriasis is frequently associated with cardiovascular diseases, metabolic diseases, and renal disorders [25][26][27][28][29][30][31][32][33][34][35][36]. Cancer risk is slightly higher in patients with psoriasis [37].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is also significantly comorbid with other autoimmune diseases, such as bullous pemphigoid [20][21][22][23][24]. Psoriasis is frequently associated with cardiovascular diseases, metabolic diseases, and renal disorders [25][26][27][28][29][30][31][32][33][34][35][36]. Cancer risk is slightly higher in patients with psoriasis [37].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors also play a crucial role in the development of psoriasis . Psoriasis is also comorbid with cardiovascular diseases, metabolic diseases and renal disorders, which represents a condition known as the inflammatory skin march …”
Section: Introductionmentioning
confidence: 99%
“…14 Psoriasis is also comorbid with cardiovascular diseases, metabolic diseases and renal disorders, which represents a condition known as the inflammatory skin march. [15][16][17][18][19][20][21][22][23] The infiltrating dermal dendritic cells produce large amounts of TNF-α and IL-23 and induce the differentiation of IL-17A-producing helper T (Th17) cells ( Figure 1). 24,25 IL-17A upregulates the proliferation of keratinocytes and downregulates the differentiation of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . showed that patients with ESRD on chronic hemodialysis are at increased risk of psoriasis 16 . Moreover, psoriatic patients are at risk of renal disease, the magnitude of which increases with worsening severity of psoriasis 1719 .…”
Section: Introductionmentioning
confidence: 99%